2016
DOI: 10.1038/srep37693
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Methodology for Engineering the Morphology of CsPbX3 Perovskite Nanocrystals under Ambient Condition

Abstract: A facile and highly reproducible room temperature, open atmosphere synthesis of cesium lead halide perovskite nanocrystals of six different morphologies is reported just by varying the solvent, ligand and reaction time. Sequential evolution of the quantum dots, nanoplates and nanobars in one medium and nanocubes, nanorods and nanowires in another medium is demonstrated. These perovskite nanoparticles are shown to be of excellent crystalline quality with high fluorescence quantum yield. A mechanism of the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
144
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(151 citation statements)
references
References 24 publications
6
144
0
1
Order By: Relevance
“…[11] Therefore, it is ap rimary concernt os earch for as ystem with high quantum yield withoutc ompromising stability. [15] Thus, capping is one of the most efficient ways to enhance thes tability of perovskite NCs in the solution [16][17][18] Oleic acid (OA) and oleylamine( OAm) are popular capping agentsr eported in the literature for the synthesis of such perovskite NCs. Properties of Bi-doped Pb halide NCs have been explored recently by somer esearch groups.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[11] Therefore, it is ap rimary concernt os earch for as ystem with high quantum yield withoutc ompromising stability. [15] Thus, capping is one of the most efficient ways to enhance thes tability of perovskite NCs in the solution [16][17][18] Oleic acid (OA) and oleylamine( OAm) are popular capping agentsr eported in the literature for the synthesis of such perovskite NCs. Properties of Bi-doped Pb halide NCs have been explored recently by somer esearch groups.…”
mentioning
confidence: 99%
“…Keepingt his in mind,w eh ave synthesized organic-inorganic hybrid iodide perovskite NCsw ith an appropriate ratio of Pb 2 + and Bi 3 + in order to maintain the formalc harge balancet hat is, (+ 2) in the B-site of these perovskites. [15,16,18,19] OA has less capping ability than OAm, buta ny of these two alone cannotp rovide as ufficient stabilityt oP bp erovskite NCs because of their poor binding with Pb 2 + . [12,13] In our previous study,w eh ave also reported the potentialo ft hese charge-balanced hybrid Pb-Bi perovskite thin films forsolar cell applications.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…"Man kann das Emphysem jetzt auch endoskopisch sehen, aber es bleibt die Frage, welchen Zusatznutzen diese Technik liefert", so Herth. Auch bei der Beurteilung der Dignität von Rundherden konnte damit bisher kein Vorteil gegenüber dem bisherigen Standard belegt werden [6].…”
Section: Konfokale Laserendomikroskopieunclassified